Colonization of rectal mucosa by microbes with antibiotic resistance markers in children with hematological malignancies - L.G. Boronina; E.V. Samatova; M.P. Kukushkina; S.A. Panova; S.S. Ustyugova; A.G. Asnovskaya (LCC «Medicine-Inform», 2021)
L.G. Boronina1,2, E.V. Samatova2, M.P. Kukushkina2, S.A. Panova2, S.S. Ustyugova2, A.G. Asnovskaya2 1Ural State Medical University, Yekaterinburg, Russian Federation 2Regional Children's Clinical Hospital, Yekaterinburg, Russian Federation Background: the steadily increasing occurrence of the infections caused by antibiotic-resistant germs and the reduction in the efficacy of antimicrobials is one of the important issues of modern medicine. Aim: to study the colonization of rectal mucosa by extended-spectrum beta-lactamase (ESBL) - producing carbapenem-resistant Enterobacterales, carbapenem-resistant Pseudomonas aeruginosa, and vancomycin-resistant Enterococci using phenotypic methods and gene tests. Patients and Methods: this study was performed from December 10, 2019, to March 30, 2020. 150 samples (131 fecal specimens and 19 rectal swabs) collected from 66 patients who were admitted to the Hematological Center were examined. All samples were inoculated into selective chromogenic media. Results: 67 strains of Enterobacterales, 71 Enterococci, and 7 P. aeruginosa were isolated. Rectal colonization by ESBL-producing Enterobacterales was identified in 17 patients (25.8%). Е. coli (13 strains, 44,8%) and K. pneumoniae (10 strains, 34,5%) prevailed. In 5 children, two or more ESBL-producing strains were isolated, i.e., Е coli plus K. pneumoniae (n=2), Е. coli plus E. cloacae (n=2), and Е. coli plus K. pneumoniae plus E. cloacae (n=1). The colonization by vancomycin-resistant Enterococci (predominantly E. faecium) was identified in 18 patients (27.3%). Vancomycin-resistant Enterococci plus ESBL-producing Enterobacterales were isolated in 9 patients (13.6%). Multidrug-resistant strains were isolated among Е. coli (n=1), K. pneumoniae (n=3), and P. aeruginosa (n=1). Conclusions: our findings demonstrate that the colonization by one and two antibiotic-resistant microbe was seen in every forth patient (25.8-27.3%) and every seventh patient (13.6%), respectively. Е coli and K. pneumoniae prevailed among Enterobacterales and E. faecium prevailed among Enterococci. Chromogenic agars are designed to examine the specimens collected from patients. Antibiotic-resistant microbes may be identified 24 hours after receiving specimen at a laboratory when using these media. Keywords: monitoring, colonization, resistance marker, microorganisms, children, hematological malignancies. For citation: Boronina L.G., Samatova E.V., Kukushkina M.P. et al. Colonization of rectal mucosa by microbes with antibiotic resistance markers in children with hematological malignancies. Russian Journal of Woman and Child Health. 2021;4(1):90-97. DOI: 10.32364/2618-8430-2021-4-1-90-97.